Point of View in Conrad’s Almayer’s Folly: A Stylistic Perspective (KEMANUSIAAN The Asian Journal of Humanities, 2018)
The aim of this paper is to examine how point of view is signaled in Conrad’s Almayer’s Folly and how it is used to exercise control over the attitudes we have of characters and events in the story. Specifically, it aims to examine who sees and who speaks in the story, whose views or ideas are being expressed as well as how characters and events are represented. As regards the characters, the focus will be on the representation of the white European self vis-a-vis the native Other. In achieving this aim, the study will utilise Halliday’s transitivity system, Fowler’s point of view model and Said’s Orientalism or discourse of Othering. Findings reveal that the features which indicate or control point of view include the system of deixis, vocabulary and transitivity structures, the use of modality as well as the various modes of speech and thought presentation. Almayer is the main focaliser in the text as the internal type of narration (narration within a character’s consciousness) is mostly accorded to him. Prolonged intrusions into Almayer’s mental faculties allow the reader to empathise with his victimised and helpless state and to distance the readers from the natives who have been depicted externally (narration from outside a character’s consciousness) in a most unsavoury manner. To some extent, an internal perspective is also accorded to the natives as it is through their perspectives that the white man’s duplicitous nature is revealed and the moral justifications for empire questioned. These are moments when Conrad registers his ambivalence towards the colonial project and empire, however his attempts are not fully realised as he invariably gets pulled back into the time-worn discourse of Othering in his representations of the Other.